2010
DOI: 10.1111/j.1556-4029.2009.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Stature Estimation from Foot Length Using Universal Regression Formula in a North Indian Population

Abstract: Stature is a significant parameter in establishing identity of an unknown. Conventionally, researchers derive regression formula separately for males and females. Sex, however, may not always be determined accurately, particularly in dismembered remains and thus the need for a universal regression formula for stature estimation irrespective of sex of an individual. The study was carried out in an endogamous group of North India to compare the accuracy of sex-specific regression models for stature estimation fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…In literature, right-and left-sided dominance in foot dimensions are reported among males and females [28,30,32,38]. A number of earlier studies, however, did not observe any bilateral differences in foot size [22,34,49,50]. RFL -right foot length, RFB -right foot breadth, LFL -left foot length, LFB -left foot breadth, RHL -right hand length, RHB -right hand breadth, LHL -left hand length, and LHB -left hand breadth.…”
Section: Discussionmentioning
confidence: 96%
“…In literature, right-and left-sided dominance in foot dimensions are reported among males and females [28,30,32,38]. A number of earlier studies, however, did not observe any bilateral differences in foot size [22,34,49,50]. RFL -right foot length, RFB -right foot breadth, LFL -left foot length, LFB -left foot breadth, RHL -right hand length, RHB -right hand breadth, LHL -left hand length, and LHB -left hand breadth.…”
Section: Discussionmentioning
confidence: 96%
“…This is calculated by dividing the longest footprint length by stature (height) and has been previously criticised as a rather blunt method resulting in high error estimates [10]. A further literature search revealed only five papers examining the relationship between footprint dimensions and stature in which results are reported in terms of correlation coefficients, regressive equations and appropriate error estimates [10][11][12][13][14]. These studies investigate the correlations of footprint widths and lengths with stature; footprint angles are not included as previous studies have shown that correlations have either an inverse relationship with stature or are non-significant [15].…”
Section: Introductionmentioning
confidence: 98%
“…The average length of the sole foot is shorter than the average length of the foot of a female Nagpur 24, 324 cm with SD 1,431 (Narde et al, 2013), New Delhi female 23.60 cm with SD 1.06 (Meena et al, 2013) Result of Pearson correlation test between foot length and height showed significant correlation between foot length and height with strong relation (r = 0,731) with significant p value (p <0,001). The results of this correlation test are higher when compared with Sri Lanka (r = 0.719) (Malik et al, 2015), Northern India (r = 0,536) (Kanchan et al, 2010), Malaysia (r = 0.662) (Khairulmazidah Et al., 2013), New Delhi (r = 0.583) (Meena et al, 2013).…”
Section: Discussionmentioning
confidence: 99%